P620 Can ustekinumab trough and antidrug antibody levels post induction predict treatment failure?. (30th January 2023) - Mccrossan, M; O'Moráin, N; Kumar, L; Rowan, C; Sheridan, J; Cullen, G; Doherty, G; Mulcahy, H
Abstract: Background: Ustekinumab (UST), a monoclonal antibody that blocks interleukins IL-12 and IL-23, is increasingly used in the treatment of Crohn's disease and Ulcerative Colitis. While therapeutic drug monitoring (TDM) is used with increasing frequency in other biologic agents, there is a paucity of data regarding the clinical utility of TDM for UST. This pilot study aimed to determine whether loss of response (LOR) and treatment failure (TF) can be predicted by post UST-induction serum trough concentrations and antibody levels. Methods: A pilot retrospective observational study of patients who received subcutaneous (SC) induction of UST, following LOR to anti-TNF, for treatment of Crohn's disease in 2016 was performed. We previously demonstrated comparable drug trough levels following SC rather than intravenous UST induction. Patients with available 74 month follow up data were included. Frozen serum samples used for this measurement were retrospectively tested for antibody levels using ELISA. Our IBD database and admissions data were analysed from 2016-2022. We recorded treatment duration, interval shortening, and treatment failure. Treatment failure was defined as switch to another biologic agent and/or surgery. Data were analysed using SPSS software [IBM], with Wilcoxon Rank Sum Test used for hypothesis testing. Results: In this pilot study, a total of 10 patients (female=1, mean age 38.5 y) met the inclusion criteria. During the 74 month follow-up period, 3 patients failed treatment (mean age 30 y) while 7 remained on UST (mean age 42 y). All patients required interval shortening (4 weekly dosing). There was no difference in Crohn's phenotype or smoking status between groups. All TF patients were switched to alternative biologic agents, with 1 patient requiring surgery. The patients who failed treatment were noted to have higher antibody levels (median 6.57 Au/ml vs 5.87 AU/ml, p=0.03) [Fig 1]. Two of these patients were noted to have lower trough levels than those who continued on UST, with one having a higher trough level (median 2.9mcg/ml vs 5.8mcg/ml, p=0.52) [Fig 2]. Conclusion: Shortening of dose interval with UST therapy in Crohn's disease is frequently required. This pilot study suggests an association between treatment failure and higher antidrug antibody levels 8 weeks post induction of UST. There was no significant difference in drug trough levels between groups. The patient with the highest trough level in the cohort failed treatment – This raises the possibility of multiple mechanisms of failure; however, it is impossible to draw conclusions given the sample size. Further studies are required to assess whether measurement of post induction antibody and drug trough levels has clinical utility in guiding treatment decisions.